ACTsmart: Guided Smartphone-Delivered Acceptance and Commitment Therapy for Chronic Pain—A Pilot Trial. Issue 2 (16th November 2020) - Gentili, Charlotte; Zetterqvist, Vendela; Rickardsson, Jenny; Holmström, Linda; Simons, Laura E; Wicksell, Rikard K
Abstract: Background: Acceptance and commitment therapy (ACT) is a behavioral health intervention with strong empirical support for chronic pain but, to date, widespread dissemination is limited. Digital solutions improve access to care and can be integrated into patients' everyday lives. Objective: ACTsmart, a guided smartphone-delivered ACT intervention, was developed to improve the accessibility of an evidence-based behavioral treatment for chronic pain. In the present study, we evaluated the preliminary efficacy of ACTsmart in adults with chronic pain. Methods: The study was an open-label pilot trial. The treatment lasted for 8 weeks, and participants completed all outcome measures at pretreatment and posttreatment and at 3-, 6-, and 12-month follow-ups, with weekly assessments of selected measures during treatment. The primary outcome was pain interference. The secondary outcomes were psychological flexibility, values, insomnia, anxiety, depressive symptoms, health-related quality of life, and pain intensity. All outcomes were analyzed using linear mixed-effects models. Results: The sample consisted of 34 adults (88% women) with long-standing chronic pain ( M =20.4 years, SD=11.7). Compliance to treatment was high, and at the end of treatment, we observed a significant improvement in the primary outcome of pain interference ( d = –1.01). All secondary outcomes significantly improved from pretreatment to posttreatment with small to large effect sizes. Improvements were maintained throughout 12 months of follow-up. Conclusion: The results of this pilot study provide preliminary support for ACTsmart as an accessible and effective behavioral health treatment for adults with chronic pain and warrant a randomized controlled trial to further evaluate the efficacy of the intervention.